PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PENERIMAAN, PENGELUARAN KAS DAN REKAM MEDIS PADA KLINIK VANVETCARE - Putri, Sukma Fitria; Wardiyanih, Giyana (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2022)
This research aims to analyze, design, implement and also test information systems for receipts, cash disbursements and medical records at the VanVetCare Clinic. The research methodology uses descriptive methods and data collection techniques used are field studies and library research data, types of data using quantitative and qualitative, as well as secondary and primary data sources.The programming language used in this information system is Visual Basic.Net and MYSQL as the database. The system development method used is the SDLC (System Development Life Cycle) approach and testing the system using a black box. The information system that has been implemented serves as a system development from using simple bookkeeping to desktop-based in processing the recording of receipts, cash disbursements and medical records. The function of this system is to overcome the problems that exist at the VanVetCare Clinic, including managing the calculation of cash receipts, cash disbursements and medical records as well as being able to maintain data security so that it is not known by all parties, which has limited user access rights from this system which is adjusted by company policy. Based on the results oftesting, black box it can be concluded that the system running 98% is said to be good.